Relatório Independente da Iniciativa de Transparência na Indústria Extractiva - EITI (Extractive Industries Transparency Initiative (EITI), 2020)
Este é o nono relatório de reconciliação dos pagamentos efectuados pelas empresas que operam na indústria extractiva e os recebimentos do Estado. Foram reconciliadas 97% das receitas tributárias provenientes da indústria extractiva. As diferenças apuradas entre os pagamentos das empresas e os recebimentos do Estado correspondem a 0,17% dos montantes confirmados pelo Estado em 2019.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Como Está Cabo Delgado? Webinar 2: Economia Política Dos Recursos Naturais - Observatório do Meio Rural (2020)
Com a entrada no novo milénio, e em virtude do aumento da procura de matérias primas nos mercados internacionais, intensifica-se um modelo de desenvolvimento assente na exploração de recursos naturais. Em Cabo Delgado emerge uma economia extractiva, fortemente dirigida para mercados externos e dependente da oscilação de preços nos mercados internacionais, que o país não tem condições de controlar. Grandes multinacionais envolvem-se numa acesa competição pelo acesso a recursos, em complexas alianças com elites nacionais, também elas em disputa entre si. Neste webinar pretende-se reflectir sobre as lógicas de acumulação aqui envolvidas, assim como o impacto que poderá ter para Moçambique em termos de receitas fiscais, e de desenvolvimento nacional.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; M - political economy analysis (PEA) / análise de economia política (AEP); extractive industries / indústrias extractivas; natural resources / recursos naturais

War in resource-rich northern Mozambique – six scenarios 2020.pdf - Santos, F. A. dos (Chr. Michelsen Institute, 2020)
Since the October 2017 attacks by alleged Islamist insurgents, commonly referred to as Ahlu Sunnah Wa-Jama and locally know as Al Shabab, on Mocimboa da Praia, it has not been entirely clear who the attackers were, what their strategic objectives are and on whose domestic and international support they rely. This paper, grounded in a historical understanding of conflict in northern Mozambique’s Cabo Delgado Province, seeks to identify possible stakeholders and scenarios in what we no longer see as an insurgency, but a war.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

“Our Lives Mean Nothing” - The Human Cost of Chinese Mining in Nagonha, Mozambique - Amnesty International (Amnesty International, 2018)
This report examines Haiyu’s conduct including what the company did or failed to do in acquiring the right to land for use of mining activity in Nagonha, what it did or failed to do in its operations in Nagonha, and what it did or failed to do in response to the villagers’ demand for compensation and resettlement following the flood. The report looks specifically at the breach of the right to adequate housing and decent living standards ensuing from Haiyu’s destruction of the wetland, and the related destruction of one-fifth of the village by the freak flood. The report also examines the Mozambican Government’s failure to protect, promote and fulfil the right to adequate housing and living standards in the village of Nagonha.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; natural resources - mining / recursos naturais - mineração; poverty / pobreza

Elite capture and the development of natural resource linkages in Mozambique - Buur, Lars; Monjane, Celso Marcos (Fairness and Justice in Natural Resource Politics, 2017)
This chapter explores these broader processes from the perspective of linkage creation in Mozambique related to mega-projects in natural resource extraction and development from a political economy perspective. From a resource fairness perspective, linkage creation is essential as it allows for a more fair distribution of opportunities for local firms to gain from large-scale natural resource investments and for learning and spillover effects to other parts of the economy. In a longer term perspective, it is a potential key source of economic transformation towards higher value added activities and more and better local employment, therefore reducing dependence on resources.
Keywords: FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; natural resources / recursos naturais

Overblown expectations of the mining sector - Economist Intelligence (Economist Intelligence, 2016)
The government of Mozambique remains confident that its mining boom is set to accelerate in the coming years, despite weak sentiment in the global mining industry. Rising coal production and an eventual rebound in global prices will spur some growth in Mozambique's mining sector in 2016‑20 but we expect that, weighed down by infrastructure deficits and non-competitive policies, it will remain a relatively small contributor to GDP growth. Mozambique has untapped coal reserves estimated to be in excess of 20bn tonnes, as well as commercial quantities of aluminium, gold, titanium, graphite and gemstones. Plus, it benefits from a long coastline and geographic proximity to mineral-hungry markets in Asia. At the peak of the commodity super-cycle, investor interest in Mozambican mining soared; the contribution of the mining sector to GDP increased from 1.6% in 2009 to 3.2% in 2013, while government earnings from the sector swelled from US$40m in 2009 to over US$1bn in 2014.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Estrutura Geológica de Moçambique - Nogar Boca (2016)
Tema: Estrutura Geológica de Moçambique A estrutura geológica de Moçambique é resultado da interacção de vários processos, sobretudo os endógenos (internos) e exógenos (externos), que se fizeram sentir e ainda sentem-se na actual região da África Austral, onde Moçambique faz parte. Do ponto de vista geológico, Moçambique apresenta duas grandes unidades geológicas: Pré-câmbrico Fanerozóico
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; natural resources / recursos naturais

Exploring Natural Resources in Mozambique: Will it be a Blessing or a Curse? - Bacuane, Aurélio; Mulder, Peter (Instituto de Estudos Sociais e Económicos (IESE), 2007)
Mozambique has considerable quantity of natural resources, of which the major part is yet to be explored. The Government of Mozambique is determined to extract and export its natural resource potential as soon as possible, supposing that this will positively contribute to economic growth and poverty reduction. However, any resources rich countries are among the poorest nations in the world, in spite of decennia-long exploration of their natural wealth. This so colled 'paradox of plenty' or 'resource curse' raises the question whether the foreseen exploration of natural resources in Mozambique will pose a serious threat rather than a blessing to its economic development. In this paper we first estimate the potential resource wealth of Mozambique in comparison to other countries. Next, we briefly review the rowing body of literature on the existence and determinants of a natural resource curse. Then we evaluate the risk of a resource curse to occur in Mozambique in the (near) future. Finally, we try to come up with suggestions to avert a Mozambican resource curse.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); extractive industries / indústrias extractivas; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; transparency / transparência